2011
DOI: 10.1177/039463201102400303
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol, Cytokines and Diseases

Abstract: A high level of cholesterol is associated with obesity, cardiovascular diseases and atherosclerosis. Immune response in atherosclerosis is mediated by chemokines which attract monocytes, leading to the innate immune response characterised by the production of cytokines. The immunoregulatory cytokines are an important bridge between innate and adductive immunity. TH1 cytokines are involved as effector T cells in inflammatory response, while TH2 cytokines can be anti-inflammatory such as IL-10 and IL-4. It is we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 113 publications
1
13
0
1
Order By: Relevance
“…Again, those rats which developed obesity had elevated oxidative stress levels while the lean rats did not. A number of studies have linked increased oxidative stress to development of atherosclerosis as it can lead to increased lipoprotein oxidation and increased cytokine release into the bloodstream (Stone, 2005;Tibolla et al, 2010;Wang et al, 2009;Saggini et al, 2011). Lastly, in a recent study from our group, we demonstrated for the first time that diet-induced obesity (DIO) elevates levels of total ROS in the mouse brain, a result which was also supported by finding a significant decrease in cortical glutathione peroxidase activity (Freeman et al, 2013).…”
Section: Effects Of a High Fat Diet And Obesity On Overall Health Andsupporting
confidence: 68%
See 1 more Smart Citation
“…Again, those rats which developed obesity had elevated oxidative stress levels while the lean rats did not. A number of studies have linked increased oxidative stress to development of atherosclerosis as it can lead to increased lipoprotein oxidation and increased cytokine release into the bloodstream (Stone, 2005;Tibolla et al, 2010;Wang et al, 2009;Saggini et al, 2011). Lastly, in a recent study from our group, we demonstrated for the first time that diet-induced obesity (DIO) elevates levels of total ROS in the mouse brain, a result which was also supported by finding a significant decrease in cortical glutathione peroxidase activity (Freeman et al, 2013).…”
Section: Effects Of a High Fat Diet And Obesity On Overall Health Andsupporting
confidence: 68%
“…First, elevated cholesterol levels are well known to occur due to an unhealthy diet/obesity (Grundy, 1997;Saggini et al, 2011;Go et al, 2013). A major component of the negative effects of a high fat diet is the high density lipoprotein (HDL)/low density lipoprotein (LDL) profile (Wang and Beydoun, 2007).…”
Section: Effects Of a High Fat Diet And Obesity On Overall Health Andmentioning
confidence: 99%
“…Many previous studies have demonstrated that elevated IL-4 production could indicate inflammatory diseases (Saggini et al, 2011). In particular, there is little questions that the elevated production of IL-4 serves as an excellent marker of IS in vitro (Kim et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The VNTR polymorphism of the IL-4 gene has been widely shown to be associated with a number of inflammatory diseases, including multiple sclerosis and idiopathic thrombocytopenic purpura as well as cerebrovascular disease (Vandenbroeck et al, 1997;Chen et al, 2007;Um and Kim, 2009). In addition, several in vitro studies showed that IL-4 regulates the JAK and STAT signal transduction pathways, consequently playing an important role in atherosclerosis and various inflammatory diseases (Saggini et al, 2011;Bao et al, 2012). Some researchers have even proposed that IL-4 has possible therapeutic potential in the treatment of inflammation-related disorders (Kleemann et al, 2008;Profumo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Эти соединения участвуют в регуляции процесса воспаления [29]. В ряде исследований отмечено сопряженное с воспалением изменение обмена холестерина [30][31][32], что может отразиться на образовании изопрена [33] и ряда других соединений (дегидроэпиандростерона, дегидроэпиандростерон-сульфата, 17-гидроксипрогестерона, андростендиона [34], 7альфа-гидроксидегидроэпиандростерона [35,36] Итак, анализ системных и внутриклеточных процессов свидетельствует о том, что при аутоиммунных патологиях можно ожидать изменений в концентрации таких ЛОС, как ацетон и изопрен, которые выделяются в составе выдыхаемого воздуха. Для проверки данного предположения были исследованы пациенты, проходившие стандартный курс лечения в Институте клинической иммунологии СО РАМН (Новосибирск).…”
Section: летучие органические соединения (лос) при аутоиммунной патолunclassified